2022
DOI: 10.2147/nss.s339898
|View full text |Cite
|
Sign up to set email alerts
|

Stress Susceptibility Moderates the Relationship Between Eveningness Preference and Poor Sleep Quality in Non-Acute Mood Disorder Patients and Healthy Controls

Abstract: Objective This study aimed to investigate the relationship between eveningness preference and poor sleep quality and eventually examine the moderation effect of stress susceptibility. Methods Individuals with non-acute major depressive disorder or bipolar affective disorder and healthy participants were recruited. The Composite Scale of Morningness (CSM) and the Pittsburgh Sleep Quality Index (PSQI) were used to evaluate chronotype and sleep quality, respectively. Eysen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
0
1
Order By: Relevance
“…Lastly, Nicassio et al [45] reported that depressive symptoms mediated 38% of the total effect of pain on sleep. While not directly related to our results, the mediators identified in these studies (e.g., depression and/or anxiety, attention to pain, pain helplessness, activation of the stress system, fatigue, and physical activity) have all been related to structural changes in the brain [31] , with sleep problems [14] , [26] , [32] , [39] , [40] , [64] , and chronic pain [2] , [12] , [34] , [42] , [56] , [61] , [63] , [71] . For example, patients with major depressive disorder have a reduction in gray matter in the left anterior cingulate cortex, as well as in the orbital, ventrolateral prefrontal and hippocampal cortices.…”
Section: Discussioncontrasting
confidence: 56%
“…Lastly, Nicassio et al [45] reported that depressive symptoms mediated 38% of the total effect of pain on sleep. While not directly related to our results, the mediators identified in these studies (e.g., depression and/or anxiety, attention to pain, pain helplessness, activation of the stress system, fatigue, and physical activity) have all been related to structural changes in the brain [31] , with sleep problems [14] , [26] , [32] , [39] , [40] , [64] , and chronic pain [2] , [12] , [34] , [42] , [56] , [61] , [63] , [71] . For example, patients with major depressive disorder have a reduction in gray matter in the left anterior cingulate cortex, as well as in the orbital, ventrolateral prefrontal and hippocampal cortices.…”
Section: Discussioncontrasting
confidence: 56%